Longitudinal changes in sputum and blood inflammatory mediators during FeNO suppression testing - Couillard, S; Shrimanker, R; Lemaire-Paquette, S; Hynes, GM; Borg, C; Connolly, C; Thulborn, S; Moran, AM; Poole, S; Morgan, S; Powell, T; Pavord, I; et al. (BMJ Publishing Group, 2022)
To explore whether exhaled nitric oxide (FeNO) non-suppression identifies corticosteroid resistance, we analysed inflammatory mediator changes during a FeNO suppression test with monitored high-intensity corticosteroid therapy. In linear mixed-effects models analysed over time, the 15 clinically-distinct ‘suppressors’ (i.e. ≥42% FeNO suppression) normalised asthma control questionnaire scores (mean±SD: 2.8±1.4 to 1.4±0.9, p<0.0001) and sputum eosinophil counts (median [IQR]: 29 [6-41] to 1 [1-5]%, p=0.0003) while significantly decreasing sputum prostaglandin D2 (254 [89-894] to 93 [49-209] pg/mL, p=0.004) and numerically decreasing other type-2 cytokine, chemokine and alarmin levels. In comparison, the 19 non-suppressors had persistent sputum eosinophilia (10 [1-67]% despite high-intensity therapy) with raised end-test inflammatory mediator levels (1.9 [0.9-2.8]-fold greater than suppressors). FeNO non-suppression during monitored treatment implies biological corticosteroid resistance.